Pathogenesis and current status of the treatment of lung cancer associated with idiopathic pulmonary fibrosis - Yuanyuan Zhang; Chang Qi; Qi Wei; Yalun Li; Panwen Tian (Respiratory Research)
Abstract Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease with chronic progressive fibrosis of unknown etiology; it is characterized by persistent fibrosis of the lungs accompanied by irreversible lung function decline and high mortality rates. A large body of evidence suggests a significant association between IPF and lung cancer (LC). IPF itself increases the risk of LC development, and LC associated with IPF often originates in areas of honeycomb lesions in IPF. In addition, there are similarities between the two diseases in terms of genetics as well as cellular molecular mechanisms; examples include genetic and epigenetic variants, fibroblast activation and proliferation, epithelial‒mesenchymal transition (EMT), abnormal mechanical forces generated in the lungs, and aberrant signaling pathway activation, which may drive the progression of pathology in both diseases. In this review, we describe in detail the epidemiological and clinical associations of LC in patients with IPF, highlight recent studies on the shared pathogenesis between IPF and LC, and discuss current advances in the treatment of LC associated with idiopathic pulmonary fibrosis.